PENGEMBANGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) MELALUI PENINGKATAN WORKPLACE SPIRITUALITY DAN ISLAMIC WORK ETHICS - Pudjihastuti, Sri Hindah; Astuti, Endang Dwi (Universitas Muria Kudus, 2019)
The purpose of the study was to determine the impact of workplace spirituality (organizational spirituality and individual spirituality) on organizational citizenship behavior (OCB), with Islamic work ethics as an intervening variable. The population in this study are professionals consisting of teaching staff and company managers. The respondents who participated were 200 professionals. The results showed that the organizational spiritual dimension has significant influence on Islamic work ethics and OCB. In addition, Islamic work ethics has a significant influence on OCB. However, the dimensions of individual spirituality have no influence on Islamic work ethics or OCB. The implication of the results of the study shows the important role of Islamic work ethics in mediating the relationship between workplace spirituality and OCB. In addition, OCB development for professionals can be done with a spirituality approach that is organizational in nature and also by increasing Islamic work ethics.